Solubility and stability enhancement of curcumin in Soluplus® polymeric micelles: a spectroscopic study. Issue 4 (20th March 2020) - Rani, Swati; Mishra, Sushil; Sharma, Manisha; Nandy, Abhishek; Mozumdar, Subho
Abstract: Polymer micelles are considered to be efficient carriers for solubilizing and stabilizing various hydrophobic drugs. In order to address the problem of poor bioavailability of curcumin, a different approach known as solid dispersion technique has been utilized to develop a formulation of curcumin with a novel amphiphilic polymer – Soluplus ® . The mechanism of interaction of curcumin with Soluplus ® has been elucidated using UV–vis absorption and steady-state fluorescence spectroscopy. At a molecular level, the reduced interaction of water molecules with curcumin, in the optimized system led to an enhancement of both absorption and emission intensities of curcumin accompanied by a hypsochromic shift in the fluorescence spectra. Furthermore, stability analysis indicated a much better environment for the drug with less than 3% degradation of curcumin in 3 days. The steady state anisotropy studies confirms the presence of a rigid environment for curcumin upon encapsulation by the polymer. The extra stability of this system can be ascribed to the formation of multiple intermolecular H-bonding interactions between curcumin and Soluplus ® which is proved by IR spectroscopy. Finally, in vitro cell viability assays indicated that it is a highly safe and effective system that could be further screened for a plethora of biological applications. Graphical Abstract: